Dramatized environmental issues : empathetic learning beyond the classroom - Teh, Kim Hong; Lee, Shok Mee; Fong, Soon Fook (2020)
Re-enacting science through creative drama is known to help students to visualize abstract scientific concepts and enhance deeper environmental understanding. The Association for Science and Mathematics Education Penang (ASMEP) has, since 2006, been organizing an annual drama competition, for secondary students, to promote awareness on environmental problems and to elicit suggestions for innovative resolutions. The drama combines the different disciplines of science, art, music, language, sports with students’ creativity to express, act and role-play their emotional with aesthetic awareness. They may empathize the feeling of despair on environmental degradation, but more importantly to elucidate suggestions to arrest lavish lifestyle, beginning from their own daily habits and roles in tackling environmental problems. This paper offers a qualitative and evaluative account of the scientific investigation, communication and cooperation skills among young learners in promoting environmental awareness based on drama competition in the last few years. It attempts to analyze the trends in the environmental issues during this period and the progress in resolving any problematic issues